Cálculo coraliforme masivo en la pielonefritis xantogranulomatosa - Sérgio Brito; Sérgio Pinho (Sociedade Galega de Medicina Interna, 2021)
Xanthogranulomatous pyelonephritis (XPN) is a rare entity and constitutes less than 1% of chronic pyelonephritis. Symptoms are frequently nonspecific and in 2/3 of cases it is associated with renal stones (coral or Staghorn calculus). 1 A 66-years-old women presented with progressive asthenia, fever, night sweating and 7-Kg weight loss over the last three months. Her medical history reported recurrent urinary infections, the last one a month before the symptoms began. On physical examination she presented with mucocutaneous pallor. Laboratory studies showed inflammatory anemia (8.9g/dL of hemoglobin), leukocytosis, neutrophilia and 95mm/h sedimentation rate. The abdominal X-ray showed massive coral calculus overlying the left renal outline (Image 1), confirmed with abdominal CT, which also revealed a non-functioning left kidney and two pyelocaliceal purulent cysts. The clinic and radiological images were consistent with the diagnosis of chronic xanthogranulomatous pyelonephritis. Blood and urine cultures were negative. Performed a CT guided percutaneous drainage with microbiological study that isolated a Proteus mirabilis. She completed a course of antibiotic followed by a left nephrectomy, with resolution of symptoms and the anemia. Anatomopathological test was later performed and confirmed the diagnosis.